Fatores associados à evolução clínica da leishmaniose visceral em crianças hospitalizadas em centro de referência de belo horizonte, 2001 a 2005 - Alexandre Sergio da Costa Braga (2007)
The objective of this study was to describe the clinical and epidemiological features, the treatment measures and the evolution of the children with visceral leishmaniasis (VL) admitted in a referral hospital in Belo Horizonte. A retrospective study was carried outthrough a systemized analysis from medical records where demographic, clinical, therapeutic and laboratorial aspects were evaluated in children hospitalized in the General Center of Pediatrics - FHEMIG, from January 2001 to December 2005. Up to twelve yearold children with compatible clinical presentation and confirmatory laboratorial examination for VL (indirect immunofluorescence (RIFI) and/or search of parasite in organs' or bone marrow samples) were included. The patients were classified in two groups: satisfactory and unsatisfactory evolution, defined by bleeding, except epistaxeand/or systemic bacterial infection and/or neutrophylus < 500 céls/mm3. From 259 medical records, 250 were eligible for this study, a total of 63.5% (250/394) of the cases of VL reported in Belo Horizonte, considering the same period and same age range. The mean age was 4 years, being 52% male. The patients who lived in urban areas represented 86.8% of the sample. Fever and splenomegaly were present in 93.6% and 98,4% of the cases respectively. The positivity of the RIFI was 95.9% and of the parasitological methods of 71.1%. The meglumine antimoniate was the first line treatment used in 96.4% of the children, with efficacy of 94.6%. Between five and 10 days after the beginning oftreatment, a regression of the liver, spleen and an improvement of the AST were observed in patients with satisfactory evolution, signs not observed in the group of patients with unsatisfactory evolution. The overall lethality was 3.6% and edema, bleeding, jaundice to the admission were factors associated to higher lethality. This study points to indicators ofclinical evolution of VL, present at the moment of admission and during the first ten days of treatment that may be useful for the clinical management of these patients.